STRATEGI PRODUK DAN DISTRIBUSI JASA PENDIDIKAN DALAM KONTEKS PENDIDIKAN MODERN - Adnan; Abdul Mu’in Bahaf; Anis Zohriah (LPPM Universitas Cipta Mandiri, 2024)
Education has undergone significant changes in recent decades, especially with the emergence of information technology and rapid social change. Therefore, educational product and service distribution strategies are important in providing effective and relevant educational experiences. This research aims to investigate product and distribution strategies for educational services in the context of modern education. The primary focus is on the role of technology, inclusivity, evaluation, and the role of educational staff in designing and managing these strategies. This research uses a descriptive qualitative approach with a literature study approach. Data were analyzed through content analysis and synthesis of relevant literature. The research results show that technology plays an important role in the distribution of modern educational services, enabling wider and more flexible access. Inclusivity and continuous evaluation are the main focus to ensure quality education. Apart from that, the role of educational staff in the development and delivery of educational services is also crucial.